THE EFFECTIVENESS OF USING CAKE-LEARNING APPLICATION ON STUDENTS’ VOCABULARY MASTERY AT MA NURUL HABIBI NW LIWUNG IN ACADEMIC YEAR - Tawali (Journal of English Education and Literature, 2024)
This investigate is pointed to examine the adequacy of utilizing the CAKE-Learning Application in upgrading students' lexicon authority at MA Nurul Habibi Nahdlatul Wathan Liwung in scholastic year 2023/2024. The objective of the ponder was to know whether the CAKE-Learning Application is an viable apparatus to make strides students' lexicon dominance. The plan of investigate strategy utilized pre-experimental consider or quantitative strategy. The subject of the think about was moment review understudy of MA Nurul Habibi Nahdlatul Wathan Liwung, comprise of seven female understudies. The method of collecting the information were pre-test and post-test. The instrument of the inquire about utilized composed test within the frame of numerous choice. The method to analyze information were cruel score, mode, middle, and t-test was utilized concurring to Sudijono, 2007: 22. The information was analyzed utilizing measurable equation of t-test. The result of information investigation appeared that the esteem of t-test was 9.756 and t-table 1.501 so the esteem of t-test is higher than t-table in noteworthiness level of 005 ((95%) with degree of flexibility 7. It implies that t-critical esteem was critical for this certainty level. And elective theory (Ha) was acknowledged and invalid theory (Ho) was rejected. Subsequently, it can be concluded that there was viable of utilizing Cake-Learning Application on students' lexicon authority at MA Nurul Habibi Nahdlatul Wathan Liwung in Scholastic Year 2023/2024.